In favor of a topological reading of curriculum policies - Macedo, Elizabeth (Education Policy Analysis Archives, 2016)
This paper is constructed around two desires that, over the years, have led me to the work of Stephen Ball - to understand politics as significant in specific historical and cultural contexts, and to conceptualize political agency beyond structural determination. From the dialogue between the notion of network in Ball´s latest works and the discourse theory as formulated by Ernest Laclau and Chantal Mouffe, I argue in favor of a topological analysis of politics. I defend it as a way to better understand both the connections between the “political contexts” and the relationship between social [topological] structure and political agency. Although my focus here is the theoretical dialogues with which I have been working, I use fragments of my research on analyzing curriculum control in recent policies in Brazil as evidence to support my argument.